2021
DOI: 10.1093/burnst/tkab011
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of functional nerve guide conduits

Abstract: Nerve guide conduits (NGCs), as alternatives to nerve autografts and allografts, have been widely explored as an advanced tool for the treatment of peripheral nerve injury. However, the repairing efficiency of NGCs still needs significant improvements. Functional NGCs that provide a more favorable microenvironment for promoting axonal elongation and myelination are of great importance. In recent years, 3D printing technologies have been widely applied in the fabrication of customized and complex constructs, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 118 publications
0
14
0
Order By: Relevance
“…This is one limitation of our branch nerve conduit. However, an increasing number of studies have found that functional nerve conduits can promote nerve regeneration [ 22 , 23 ]. For instance, we previously found that cell-loaded or drug-loaded nerve conduits were superior to nonfunctional nerve conduits and had regeneration ability comparable to that of autografts [ 15 , 16 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is one limitation of our branch nerve conduit. However, an increasing number of studies have found that functional nerve conduits can promote nerve regeneration [ 22 , 23 ]. For instance, we previously found that cell-loaded or drug-loaded nerve conduits were superior to nonfunctional nerve conduits and had regeneration ability comparable to that of autografts [ 15 , 16 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since remnant particles may cause a foreign body reaction, [266] DIW allows continuous printing without remnant particles on the printing bed attractively. To obtain a more accurate bifurcated Yshaped NGC or more permeable NGC for hindering neuroma formation, [268][269][270] imaging technology and SLIS [210] can apace custom the model. Besides, selective laser sintering (SLS) [208,220] has been widely used for high mechanical strength scaffolds in bone tissue engineering, but it is rarely applied to fabricate NGC.…”
Section: D Printingmentioning
confidence: 99%
“…Currently, indirect 3D bioprinting has made progress in both hard and soft tissue engineering systems. Some specific tissue constructs such as functional nerve guide conduits, human knee meniscal scaffolds, sized vascular grafts, can be successfully produced in laboratories as proof of concept (Schöneberg et al, 2018;Huang et al, 2021;P B et al, 2022). At the same time, with the assistance of sacrificial molds, materials that are traditionally difficult to print can be utilized to manufacture fine structures.…”
Section: Indirect 3d Bioprinting For Tissue Vascularization Vasculari...mentioning
confidence: 99%